2022
DOI: 10.3390/nano12040721
|View full text |Cite
|
Sign up to set email alerts
|

An Array of Flag-Type Triboelectric Nanogenerators for Harvesting Wind Energy

Abstract: Harvesting wind energy from the ambient environment is a feasible method for powering wireless sensors and wireless transmission equipment. Triboelectric nanogenerators (TENGs) have proven to be a stable and promising technology for harvesting ambient wind energy. This study explores a new method for the performance enhancement and practical application of TENGs. An array of flag-type triboelectric nanogenerators (F-TENGs) for harvesting wind energy is proposed. An F-TENG consists of one piece of polytetrafluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…However, due to the electrostatic shielding, the overall electric output of the single-electrode TENG is only half of the dual-electrodes mode. However, the advantage of single-electrode TENG affords it a wide range of application prospects in movement monitoring and energy collection of water droplets, intelligent sensing, human-computer interaction and other fields [ 39 , 40 ].…”
Section: The Mechanism and Structure Design Of Tengmentioning
confidence: 99%
“…However, due to the electrostatic shielding, the overall electric output of the single-electrode TENG is only half of the dual-electrodes mode. However, the advantage of single-electrode TENG affords it a wide range of application prospects in movement monitoring and energy collection of water droplets, intelligent sensing, human-computer interaction and other fields [ 39 , 40 ].…”
Section: The Mechanism and Structure Design Of Tengmentioning
confidence: 99%
“…The triboelectric nanogenerator (TENG), invented by Wang et al in 2012, can effectively harvest mechanical energy from the environment. [15] It has been widely studied for harvesting wind, [16][17][18][19] vibration, [20][21][22] and wave energies. [23][24][25][26][27] Zi et al have systematically compared the output performance of the EMG and the TENG with low-frequency input.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [ 38 ] reported a humidity-resistant, wind-direction-adapting flag-type TENG capable of collecting wind energy in the environment and serving as a self-powered wind-speed and wind-direction sensor. On the basis of the above, Zhao et al [ 39 ] modified the surface morphology of PTFE by sandpaper-grinding to improve the output performance, and systematically studied the effect of horizontal and vertical array arrangement on power output. However, the output performance of the single flag-type TENG needs to be improved.…”
Section: Introductionmentioning
confidence: 99%